Drivers of fisheries and their management in the lakes of Pokhara Valley, Nepal - Md Akbal Husen; Tek Bahadur Gurung; Agni Prasad Nepal (Journal of Fisheries, 2019)
Inland fisheries provide food security, livelihood and well-being to community. Fisheries management of lakes is a complex process, influenced by many drivers. In this study the driver of fisheries of lakes of Pokhara Valley were determined through interview of Jalari fishers, key informants and field visits from July 2016 to June 2017. Key drivers were illegal fishing, siltation, loss of fish habitat, water pollution and accelerated eutrophication, intensification of agriculture, biological invasion and developmental works. These drivers have played a key role in changing lake characteristics including lake size, water quality, water depth and natural food availability which subsequently affected the cage aquaculture and capture fisheries of the lake. This paper included an insight of these drivers along with strategy to mitigate them to ensure sustainable fisheries.